Phenotypic Modulation of Intima and Media Smooth Muscle Cells in Fatal Cases of Coronary Artery Lesion - Hiroyuki Hao; Giulio Gabbiani; Edoardo Camenzind; Matthew Bacchetta; Renu Virmani; Marie‐Luce Bochaton‐Piallat (2005)
Characterize the phenotypic features of media and intima coronary artery smooth muscle cells (SMCs) in mildly stenotic plaques, erosions, stable plaques, and in-stent restenosis.Expression of alpha-smooth muscle actin (alpha-SMA), smooth muscle myosin heavy chains (SMMHCs), and smoothelin was investigated by immunohistochemistry followed by morphometric quantification. The cross-sectional area and the expression of cytoskeletal proteins in the media were lower in restenotic lesions and, to a lesser extent, in stable plaques compared with mildly stenotic plaques and erosions. An important expression of alpha-SMA was detected in the intima of the different lesions; moreover, alpha-SMA staining was significantly larger in erosions compared with all other conditions. In the same location, a striking decrease of SMMHCs and a disappearance of smoothelin were observed in all situations.Medial atrophy is prevalent in restenotic lesions and stable plaques compared with mildly stenotic plaques and erosions. Intimal SMCs of all situations exhibit a phenotypic profile, suggesting that they have modulated into myofibroblasts (MFs). The high accumulation of alpha-SMA-positive MFs in erosions compared with stable plaques correlates with the higher appearance of thrombotic complications in this situation.